2020
DOI: 10.1002/pd.5854
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound detected prenatal hyperechoic lung lesions and concordance with postnatal findings: A common aspect for multiple diagnoses

Abstract: Objective Hyperechoic lung lesions are largely detected prenatally but their underlying etiology is still poorly defined. The aim of the study was to determine the concordance between pre and postnatal diagnosis of hyperechoic lung lesions. Methods Prenatal ultrasound (US) evaluation was performed by a fetal medicine specialist. Postnatal diagnosis was based on CT‐scan. Pre‐ and postnatal features were retrieved from medical charts. Results Seventy five patients were included from January 2009 to December 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…previously described in congenital lobar overinflation on MRI 1,6 . Moreover, bronchiectasis may be located distally in a pulmonary lobe and could therefore be overlooked.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…previously described in congenital lobar overinflation on MRI 1,6 . Moreover, bronchiectasis may be located distally in a pulmonary lobe and could therefore be overlooked.…”
Section: Discussionmentioning
confidence: 84%
“…Echogenic lung results from fluid retention in the bronchial tree and pulmonary alveoli, with an increase in volume of the downstream segment. Bronchiectasis can be visualized at the hilum in cases of proximal atresia (obstruction of a stem bronchus) as previously described in congenital lobar overinflation on MRI 1,6 . Moreover, bronchiectasis may be located distally in a pulmonary lobe and could therefore be overlooked.…”
Section: Introductionmentioning
confidence: 87%
“…As most PS cases remain asymptomatic after birth, intrusive pathological diagnosis can hardly be obtained in a large surveillance system like CBDMN. Some comparative studies have revealed a high concordance (> 90%) between prenatal ultrasound diagnosis and postoperative pathological confirmation [ 4 , 45 ]. For the past 30 years, sonographic technology has been widely used in China for the prenatal and postnatal detection of structural malformations, including PS [ 23 , 46 ].…”
Section: Discussionmentioning
confidence: 99%